2022
DOI: 10.3389/fnins.2022.909149
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Electrical Stimulation: Role and Clinical Impact on Chronic Nausea and Vomiting

Abstract: Gastric electrical stimulation (GES) is currently used as an alternative treatment for medically refractory gastroparesis. GES has been initially developed to accelerate gastric motility, in order to relieve the symptoms of the patients. Subsequent studies, unfortunately, failed to demonstrate the acceleration of gastric emptying using high-frequency stimulation – low energy stimulation although the technique has shown a clinical impact with a reduction of nausea and vomiting for patients with gastroparesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…[36][37][38] Likewise, GES has been shown to be effective in both patients with delayed or normal gastric emptying prior implantation. [37][38][39] In contrast, G-POEM accelerates gastric emptying by increasing pylorus diameter and distensibility. 12,[40][41][42][43][44] A first cohort study of combined GES and surgical pyloroplasty (n = 24)…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[36][37][38] Likewise, GES has been shown to be effective in both patients with delayed or normal gastric emptying prior implantation. [37][38][39] In contrast, G-POEM accelerates gastric emptying by increasing pylorus diameter and distensibility. 12,[40][41][42][43][44] A first cohort study of combined GES and surgical pyloroplasty (n = 24)…”
Section: Discussionmentioning
confidence: 98%
“…GES has been shown to relieve nausea and vomiting through central pathway, 33–35 without accelerating gastric emptying 36–38 . Likewise, GES has been shown to be effective in both patients with delayed or normal gastric emptying prior implantation 37–39 . In contrast, G‐POEM accelerates gastric emptying by increasing pylorus diameter and distensibility 12,40–44 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most validated alternative treatment to G‐POEM in severe refractory gastroparesis is gastric electrical stimulation (GES). 111 In randomized controlled trials, GES has shown a significant reduction of nausea and vomiting in patients with refractory gastroparesis. 112 There are no criteria to guide the choice of treatment, which therefore depends on the local possibilities and experience.…”
Section: Alternative Treatments and Future Directionsmentioning
confidence: 99%
“…1 Gastric electrical stimulation (GES) has proven to be effective in the treatment of refractory chronic nausea and vomiting. 6 This efficacy has been proven in patients with normal and delayed gastric emptying. 7 In 2019, a multicenter cohort study of 319 gastroparesis patients concluded a significant improvement in nausea and vomiting within 48 weeks after the implantation of GES.…”
Section: Introductionmentioning
confidence: 99%
“…10 The battery life is 5 to 10 years, but it can be replaced if necessary. 6 Therefore, many female patients remain with an active GES device for many years.…”
Section: Introductionmentioning
confidence: 99%